Phenotypes and genotypes in individuals with SMC1A variants. Issue 8 (26th May 2017) - Huisman, Sylvia; Mulder, Paul A.; Redeker, Egbert; Bader, Ingrid; Bisgaard, Anne‐Marie; Brooks, Alice; Cereda, Anna; Cinca, Constanza; Clark, Dinah; Cormier‐Daire, Valerie; Deardorff, Matthew A.; Diderich, Karin; et al.
Abstract : SMC1A encodes one of the proteins of the cohesin complex. SMC1A variants are known to cause a phenotype resembling Cornelia de Lange syndrome (CdLS). Exome sequencing has allowed recognizing SMC1A variants in individuals with encephalopathy with epilepsy who do not resemble CdLS. We performed an international, interdisciplinary study on 51 individuals with SMC1A variants for physical and behavioral characteristics, and compare results to those in 67 individuals with NIPBL variants. For the Netherlands all known individuals with SMC1A variants were studied, both with and without CdLS phenotype. Individuals with SMC1A variants can resemble CdLS, but manifestations are less marked compared to individuals with NIPBL variants: growth is less disturbed, facial signs are less marked (except for periocular signs and thin upper vermillion), there are no major limb anomalies, and they have a higher level of cognitive and adaptive functioning. Self‐injurious behavior is more frequent and more severe in the NIPBL group. In the Dutch group 5 of 13 individuals (all females) had a phenotype that shows a remarkable resemblance to Rett syndrome: epileptic encephalopathy, severe or profound intellectual disability, stereotypic movements, and (in some) regression. Their missense, nonsense, and frameshift mutations are evenly spread over the gene. We conclude that SMC1A variants can result in a phenotype resembling CdLS and a phenotype resembling Rett syndrome. Resemblances between the SMC1A group and the NIPBL group suggest that a disturbed cohesin function contributes to the phenotype, but differences between these groups may also be explained by other underlying mechanisms such as moonlighting of the cohesin genes.